1987
DOI: 10.1093/bja/59.4.431
|View full text |Cite
|
Sign up to set email alerts
|

Propofol or Thiopentone: Effects on Intraocular Pressure Associated With Induction of Anaesthesia and Tracheal Intubation (Facilitated With Suxamethonium)

Abstract: Changes in intraocular pressure (IOP) were studied in patients given propofol 2.1 mg kg-1 (n = 30) or thiopentone 4.9 mg kg-1 (n = 30) followed by suxamethonium 1.0 mg kg-1 and tracheal intubation. Half the patients in each group received an additional smaller dose of the same induction agent (propofol 1.0 mg kg-1 or thiopentone 2.0 mg kg-1) immediately before intubation. Both agents produced significant decreases in IOP which were slightly more marked with propofol. The administration of suxamethonium produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1
3

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 6 publications
0
21
1
3
Order By: Relevance
“…However, the insignificant IOP changes after propofol administration observed in the present study were probably due to the lower dose of doi: 10.17221/115/2016-VETMED propofol used. Our and Hofmeister's findings are not in agreement with those reported in humans, where propofol decreased IOP by 40% (Mirakhur et al 1987).…”
Section: Discussioncontrasting
confidence: 99%
“…However, the insignificant IOP changes after propofol administration observed in the present study were probably due to the lower dose of doi: 10.17221/115/2016-VETMED propofol used. Our and Hofmeister's findings are not in agreement with those reported in humans, where propofol decreased IOP by 40% (Mirakhur et al 1987).…”
Section: Discussioncontrasting
confidence: 99%
“…39 Induction agents (e.g., propofol) cause a decrease in the pressures of up to 40 percent. 40 It is possible that the low pressures recorded in both the control and operated sides in six patients were related to the propofol used as the induction agent in all patients in this study.…”
Section: Discussionmentioning
confidence: 89%
“…There are two other parameters potentially influencing IOP measurements, namely body position [15] and the influence of anaesthesia [22][23][24]. We believe both to be irrelevant in our investigation, as all our measurements [3] recently demonstrated that the IOP decreased significantly during the first 8 minutes of general anaesthesia in children.…”
Section: Discussionmentioning
confidence: 96%